1993
DOI: 10.1152/ajpcell.1993.265.1.c15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin-converting enzyme inhibition on mitochondrial number in the aging mouse

Abstract: To investigate the effects of angiotensin-converting enzyme (ACE) inhibitors on the cellular function and structure in a variety of organs during the aging process, one hundred CF1 mice were divided into four groups of 25 animals each. Groups A, B, and C received enalapril in drinking water from weaning until the age of 24 mo. Doses administered were (in mg/l): group A, 20; group B, 10; group C, 5. Group D is the control. Animals were killed, and morphometric studies were performed in heart, kidney, liver, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…We have previously shown [16], that the reduction in the number of mitochondria that occurs with age in mouse hepatocytes and miocardiocytes was prevented by chronic treatment with enalapril. In this paper, we show that enalapril and captopril increase the activities of CuZn-SOD, Mn-SOD, and SeGPx in mouse liver.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown [16], that the reduction in the number of mitochondria that occurs with age in mouse hepatocytes and miocardiocytes was prevented by chronic treatment with enalapril. In this paper, we show that enalapril and captopril increase the activities of CuZn-SOD, Mn-SOD, and SeGPx in mouse liver.…”
Section: Discussionmentioning
confidence: 97%
“…In previous work, we found that mice chronically treated with enalapril, a non-sulfhydryl containing ACE inhibitor, showed a reduction in myocardial and glomerular sclerosis and an increase in the number of mitochondria in myocardiocytes and hepatocytes, which was correlated with an increase in their survival, when compared with untreated controls [16]. Considering that it has been widely postulated that ROS are causally involved in the aging process, we hypothesized that enalapril might have altered the prooxidant/antioxidant balance, in favor of the latter, protecting cells from oxidative damage.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…17 In the same study it was also demonstrated that enalapril treatment prevented glomerular enlargement and mesangial expansion. 17 In addition to hyperfiltration, it has recently been shown that glomerular enlargement and mesangial expansion are major factors in the development of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, we showed that the decrease in glomerular and myocardial sclerosis in those animals was related to an increase in the number of hepatic and cardiac mitochondria. 17 These findings suggest a relation between the deletion of the mitochondrial genome and aging. In the present study we provide evidence that natural aging is associated with intraglomerular expression of a-SM actin and that treatment with enalapril from early life prevents the early changes associated with glomerular injury and the expression of a-SM actin in the glomerulus.…”
mentioning
confidence: 89%